(untitled) (Web of Teachers: Inderscience Research, 2024)
This article delves into the derivational potential of Latin and Greek word-formation elements in the English language. By analyzing the linguistic and cultural impacts of borrowing from these classical languages, the study aims to elucidate how English has enriched its vocabulary and semantic nuances through derivational processes. Through a comprehensive literature review, methodological insights, and empirical findings, this research sheds light on the intricate interplay between linguistic borrowing and cultural assimilation in shaping the lexicon of English.